2021
DOI: 10.2486/indhealth.2021-0130
|View full text |Cite
|
Sign up to set email alerts
|

Reliability and validity of the Japanese version of the psychological safety scale for workers

Abstract: Although an increasing number of studies on psychological safety at workplaces has been conducted in both western and eastern countries, there are few empirically validated measures in Japan. Our purpose was to investigate the validity and reliability of the Japanese version of the Psychological Safety Scale. Japanese workers were invited to participate in online surveys at baseline and at one-month follow-up (N=320).The Psychological Safety Scale was translated into Japanese according to international guideli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(18 citation statements)
references
References 56 publications
1
17
0
Order By: Relevance
“…showing the positive association of PS with supervisor support, co-workers' support, and organizational factors 6 . A supportive work environment may make workers feel safe in taking interpersonal risks.…”
Section: Hypothesis Testing For Convergent Validitymentioning
confidence: 95%
See 4 more Smart Citations
“…showing the positive association of PS with supervisor support, co-workers' support, and organizational factors 6 . A supportive work environment may make workers feel safe in taking interpersonal risks.…”
Section: Hypothesis Testing For Convergent Validitymentioning
confidence: 95%
“…In non-HCWs, a previous study suggested that being allowed to express opinions and actually doing so were different experiences among Japanese workers 6 . Leaders' willingness to allow and encourage employees to speak up and employees' perceptions of doing so may both be required PS in non-HCWs.…”
Section: Hypothesis Testing For Convergent Validitymentioning
confidence: 99%
See 3 more Smart Citations